THE ANALYSIS OF MIND MAPPING ON WRITING SKILLS IN EFL CLASSROOMS STUDENTS’ PERCEPTION (INTERNATIONAL SEMINAR, 2024)
This qualitative study explores students'perceptions of mind mapping as a tool for enhancingwriting skills in English as a Foreign Language (EFL)classrooms. Through semi-structured interviews and focusgroup discussions with twenty intermediate EFL learners,the research investigates how mind mapping influencestheir writing processes, creativity, and overall engagementwith the language. The findings reveal that students viewmind mapping as a valuable strategy that aids in organizingtheir thoughts, generating ideas, and improving theirconfidence in writing. Participants also express a preferencefor visual learning tools, highlighting the role of mindmapping in making the writing process more enjoyable andless intimidating. This study contributes to theunderstanding of student-centered approaches in languageeducation and emphasizes the importance of incorporatinginnovative strategies to foster effective writing skills